Pragmatic Properties of Limited Vocabulary in Uzbek Language (Journal of Pedagogical Inventions and Practices, 2022)
This article is devoted to the study of the pragmatic features of limited vocabulary. It explains the appearance of limited vocabulary in works of art and movies, that is, the features of jargon and slang. The need to scientifically study the scope, ie pragmatics, of such words was discussed. The article is scientifically based on slang and slang words and related information. It highlights how powerful the power of words in our speech is.